2014
DOI: 10.1007/s10388-014-0447-3
|View full text |Cite
|
Sign up to set email alerts
|

Septic shock-related acute esophageal necrosis and stenosis: three cases of acquired esophageal stenosis presenting a similar clinical course

Abstract: We present a case of acute esophageal necrosis (AEN) and two acquired esophageal stenosis cases which showed a similar clinical course after an episode of septic shock. Extensive stenosis of the distal esophagus developed in all cases, which were refractory to dilation therapy and required surgical intervention. The etiology of the latter two cases was deduced from the stenosis after septic shock-induced AEN. Since the diagnosis of AEN is based on its characteristic endoscopic findings which can only be confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
(9 reference statements)
0
8
0
Order By: Relevance
“…Esophageal stricture is a complication in the chronic phase of AEN. When reviewing literature, 20 of 164 patients progressed to esophageal stricture within 3 weeks to 2 months after the onset of AEN [8, 1220]. The initial treatment in most AEN-induced stricture cases was endoscopic balloon dilation (EBD).…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal stricture is a complication in the chronic phase of AEN. When reviewing literature, 20 of 164 patients progressed to esophageal stricture within 3 weeks to 2 months after the onset of AEN [8, 1220]. The initial treatment in most AEN-induced stricture cases was endoscopic balloon dilation (EBD).…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature found that 19 of 163 patients with AEN progressed to esophageal stricture 3 weeks to 2 months after the onset of AEN [3, 613]. Gurvits et al reported that coronary artery disease, recent surgery, and gastroduodenal pathology may be associated with esophageal stricture [1].…”
Section: Discussionmentioning
confidence: 99%
“…Gurvits et al reported that coronary artery disease, recent surgery, and gastroduodenal pathology may be associated with esophageal stricture [1]. Shichinohe et al [3] reported three cases of acquired esophageal stricture after AEN with septic shock and hypothesized that severe hypoperfusion of the middle to low esophagus due to septic shock may cause esophageal stricture after AEN. Our patient developed a state of severe septic shock and had both a hiatal hernia and duodenal ulcer at the time of the AEN diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations